2013
DOI: 10.1007/s00540-013-1725-2
|View full text |Cite
|
Sign up to set email alerts
|

Not only bupivacaine but also propofol is sinking in lipid?

Abstract: To the Editor:We read with great interest the recent article [1] and editorial [2] by Oda and Ikeda in this journal. The authors clearly demonstrated the effect of lipid emulsion on central nervous system abnormalities induced by bupivacaine toxicity using the unique experimental in vivo animal model. Although many anesthesiologists in developed countries, including Japan, would prefer to choose safer and long-acting local anesthetics, e.g., ropivacaine, basic research on the mechanism of drug toxicity and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…We previously found that dilution with a crystalloid solution of Diprivan® enhanced the hypnotic potency of propofol, whereas simultaneous administration of lipid diminished its potency [15,16]. Propofol is a highly lipophilic solvent that is distributed as an emulsified micelle solution [17].…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that dilution with a crystalloid solution of Diprivan® enhanced the hypnotic potency of propofol, whereas simultaneous administration of lipid diminished its potency [15,16]. Propofol is a highly lipophilic solvent that is distributed as an emulsified micelle solution [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear explanation for the results concerning the effect of the concentration. In the preliminary and laboratory animal experiments, we found opposite results that the diluted propofol showed greater potency [ 12 ]. In clinical settings, variability of the effect of propofol might absolutely depend on pathophysiological backgrounds [ 13 ] and the difference of formulations might be negligible.…”
Section: Discussionmentioning
confidence: 99%